Suppression of rotating machine shaft-line torsional vibrations by a driving asynchronous motor using two advanced control methods - Hańczur, Paweł; Szolc, Tomasz; Konowrocki, Robert (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Many industrial rotating machines driven by asynchronous motors are often affected by detrimental torsional vibrations. In this paper, a method of attenuation of torsional vibrations in such objects is proposed. Here, an asynchronous motor under proper control can simultaneously operate as a source of drive and actuator. Namely, by means of the proper control of motor operation, it is possible to suppress torsional vibrations in the object under study. Using this approach, both transient and steady-state torsional vibrations of the rotating machine drive system can be effectively attenuated, and its precise operational motions can be assured. The theoretical investigations are conducted by means of a structural mechanical model of the drive system and an advanced circuit model of the asynchronous motor controlled using two methods: the direct torque control – space vector modulation (DTC-SVM) and the rotational velocity-controlled torque (RVCT) based on the momentary rotational velocity of the driven machine working tool. From the obtained results it follows that by means of the RVCT technique steady-state torsional vibrations induced harmonically and transient torsional vibrations excited by switching various types of control on and off can be suppressed as effectively as using the advanced vector method DTC-SVM.